Socio-economic Impact of Grameen Bank Income Generating Loans on Rural Women of Tangail District - Labani, SA; Islam, MZ; Hafeez, ASMG (Journal of Environmental Science and Natural Resources, 2016)
A study was conducted to examine the socio-economic impact of Grameen Bank(GB) income generating loans on rural women in selected areas of Tangail district. The study was conducted to examine the impact of loan on the livelihood improvement of women borrowers. Sixty respondents were purposively selected from 3 villages namely Hemnagar, Volapara and Shimlapara of which 10 were engaged in farming, 21 were engaged in livestock rearing, 19 were engaged in petty business, 5 were engaged in tailoring and 5 were indirectly engaged in van/rickshaw pulling. Tabular and statistical analyses were applied for achieving the objectives. In the study area, higher proportions (55 percent) of women were middle aged and 93 percent were married. About 75 percent had signature ability, 18 and 7 percent studied up to primary and secondary level respectively. Average family size of the respondents was 5.36, average annual income and saving of the respondents were Tk. 65958 and 8770, respectively. Overall income and saving change by taking loan from GB were 36.04% and 68.69% respectively. There was remarkable increase in attitudes and opportunities of the respondents after joining the GB. The findings show that GB loan brought about positive impact on livelihood improvement of the borrowers. J. Environ. Sci. & Natural Resources, 8(2): 135-139 2015